2018
DOI: 10.2169/internalmedicine.9556-17
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotic Syndrome with Thrombocytopenia, Lymphadenopathy, Systemic Inflammation, and Splenomegaly

Abstract: Nephrotic syndrome can be caused by various diseases, from primary kidney diseases to systemic diseases. A kidney biopsy is useful for confirming the causes of nephrotic syndrome and in its management. We herein describe a case of nephrotic syndrome with thrombocytopenia, lymphadenopathy, systemic inflammation, splenomegaly, kidney enlargement, and progressive renal insufficiency. A kidney biopsy showed endothelial swelling with mild interstitial fibrosis and tubular atrophy. This case met the diagnostic crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…The median creatinine level at the time of renal biopsy was 2.13 mg/dL [1.25; 2.52], and urinary sediment was present in most cases (glomerular hematuria in 13 cases and proteinuria over 1 g per gram of creatinine or per day in 7 cases). Two cases were described as having nephrotic syndrome (5, 14). Nine cases (47%) presented with severe renal insufficiency requiring hemodialysis and 11 cases (58%) needed treatment beyond corticosteroid monotherapy to induce disease response (e.g., plasma exchange, tocilizumab, intravenous immunoglobulin, and rituximab).…”
Section: Review Of Literaturementioning
confidence: 99%
“…The median creatinine level at the time of renal biopsy was 2.13 mg/dL [1.25; 2.52], and urinary sediment was present in most cases (glomerular hematuria in 13 cases and proteinuria over 1 g per gram of creatinine or per day in 7 cases). Two cases were described as having nephrotic syndrome (5, 14). Nine cases (47%) presented with severe renal insufficiency requiring hemodialysis and 11 cases (58%) needed treatment beyond corticosteroid monotherapy to induce disease response (e.g., plasma exchange, tocilizumab, intravenous immunoglobulin, and rituximab).…”
Section: Review Of Literaturementioning
confidence: 99%
“…The increased levels of serum IL-6 and VEGF could increase permeability of the arteriolar wall and glomerular capillaries and could be associated with endothelial injuries in patients with TAFRO syndrome. Although mild proteinuria can be observed in patients with TAFRO syndrome, Nakamori et al have recently reported the first case of TAFRO syndrome manifesting nephrotic syndrome [56]. In their case, manifestations of TMA and double contour were absent although endothelial swelling, mild interstitial inflammation, fibrosis, and tubular atrophy were observed.…”
Section: Discussionmentioning
confidence: 93%
“…Investigating renal pathology is important for understanding the pathophysiology of TAFRO syndrome. However, only a few case reports with kidney biopsy results have been published in the literature [49,53,55,56]. Performing kidney biopsy during the acute phase of TAFRO syndrome could be difficult because of the presence of massive ascites, presence of thrombocytopenia, and difficulty with placement in the prone position because of dyspnea.…”
Section: Discussionmentioning
confidence: 99%
“…Renal dysfunction is very common in patients with TAFRO syndrome, with the two main patterns of renal pathological changes being described in recent literature as TMA-like glomerulopathy and MPGN [ 19 28 ]. On light microscopy, MPGN and chronic TMA share similar histological patterns: mesangial proliferation, double contours and endocapillary proliferation.…”
Section: Resultsmentioning
confidence: 99%